Monitoring agricultural sector performance, growth, and poverty in Africa - Johnson, Michael E.; Omilola, Babatunde; Flaherty, Kathleen; Makombe, Tsitsi; MacNeil, Marcia; Horowitz, Leah (International Food Policy Research Institute, 2008)
Agriculture provides the backbone of the economy in many African countries. Moreover, the majority of the rural poor depend on agriculture either directly or indirectly for their livelihoods.1 Developing agriculture specifi cally and the rural sector more broadly are key components of Africa’s pathway out of poverty. Yet in the last decades of the 20th century, agriculture in Sub-Saharan Africa (SSA) suff ered from a tragedy of political inattention and disinvestment.